How Prepared Is Africa for the COVID-19 Pandemic Response? The Case of Ethiopia - Tolu LB; Ezeh A; Feyissa GT (Dove Medical Press, 2020)
Lemi Belay Tolu,1 Alex Ezeh,2 Garumma Tolu Feyissa3 1Department of Obstetrics and Gynecology, Saint Paul Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2Dornsife School of Public Health, Drexel University, Philadelphia, PA, USA; 3Department of Health, Behavior and Society, Jimma University, Jimma, EthiopiaCorrespondence: Garumma Tolu Feyissa Email garummatolu@yahoo.comAbstract: The coronavirus disease 2019 (COVID-19) is an ongoing pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The objective of this research communication is to describe the general epidemic preparedness of Ethiopia using “Ready score” criterion that was developed by PreventEpidemics.org. The ReadyScore criteria is used to determine whether a country is prepared to find, stop, and prevent epidemics. This set of criteria advises countries to take tailored measures based on their actual circumstances. Ethiopia’s preparedness as assessed using the ReadyScore criteria is 52%, which indicates that much work is expected from the country. Based on the current situation of Ethiopia’s epidemic preparedness, the currently increasing trend in the number of COVID-19 cases and the current situation of Ethiopia in relation to its preparedness to mitigate the pandemic of Covid-19, we recommend (a) mass communication and community mobilization, (b) social distancing measures, (c) sanitary measures, (d) maximizing case tracing and detection, (e) developing detailed operational guidelines on preventive measures across different businesses, organizational and community settings, (f) measures for sustaining essential health services and (g) proactive measures to sustain life during the lockdown.Keywords: Covid-19, severe acute respiratory syndrome coronavirus 2, SARS-CoV-2, PANDEMICS, Africa, Ethiopia